Saint-Georges, Caribbean Contradances, and the French School of Violin - Tardif, Guillaume (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2025)
From a violin history perspective, our understanding of Saint-Georges’ career is unfortunately limited by incomplete and scattered information. In this article, I explore three main questions related to Saint-Georges, two of which are hypothetical. First, I question whether a Rondeau by Saint-Georges could be connected to contemporary Caribbean contradance music. Second, I consider whether Saint-Georges’ prolonged absence from the repertoire can be attributed to his relative position within the French Violin School. Finally, after noticing similar-sounding passages in Saint-George’s symphonies concertantes from 1778-1779 and Mozart’s Sinfonia concertante in E-flat (K. 364) of 1779, I wonder whether Mozart drew inspiration from Saint-Georges’ music—and, if so, how he could have adapted it for his own purposes